Glucose-2-oxidase activity and accumulation of D-arabino-2-hexosulose in cultures of the basidiomycete Oudemansiella mucida - Volc, J; Sedmera, P; Musílek, V (Folia microbiologica, 1978)
Submerged cultures of the basidiomycete Oudemansiella mucida, strain III, accumulate D-arabino-2-hexosulose. The maximum yields during cultivations in shaker flasks or in a laboratory fermentor are 6--12 and 15 mg/ml, respectively (20--50% conversion of substrate glucose). The accumulation is transient, the aldoketose being again utilized after glucose exhaustion. Its production is stimulated by fluoride ions. The enzyme responsible for the C(2)-specific oxidation of D-glucose acts as an intracellular oxidase with a maximum activity in the exponential phase of growth. D-arabino-2-Hexosulose was also detected in the cultivation medium of the wood-rotting fungi Pleurotus ostreatus, Laetiporus sulphureus, and Phellinus abietis.
Keywords: Basidiomycota; Hexoses; Glucose Oxidase; hexosy; fluorid sodný; fermentace; Fermentation; Sodium Fluoride; glukosaoxidasa